IL-17 Expression in the Perifollicular Fibrosis in Biopsies From Lichen Planopilaris. (27th December 2022) - Miteva, Mariya; Nadji, Mehrdad; Billero, Victoria; LaSenna, Charlotte; Nattkemper, Leigh; Romanelli, Paolo
Abstract : Background: Lichen planopilaris (LPP) is a primary lymphocytic cicatricial alopecia for which therapy is often ineffective and there is no cure. Objectives: Looking for a new targetable molecule in the treatment of LPP, we sought to verify whether IL-17 expression is increased in scalp biopsies from patients with active scalp lesions of LPP. Methods: Horizontal sections of hematoxylin and eosin–stained slides from 40 scalp biopsies of active LPP were retrospectively collected and stained with the monoclonal antibody against IL-17 (Abcam, Cambridge, MA; ab79056, dilution 1:100). Twenty biopsies from patients with chronic telogen effluvium served as controls because of their morphological resemblance to the normal scalp. Statistical analysis was performed using IBM SPSS Statistics for Windows (IBM Corporation, Armonk, NY). Results: The main finding was the positive cytoplasmic expression of IL-17 in the perifollicular fibrosis of the affected follicles in LPP which was statistically significant compared with the controls ( P < 0.0001). The labeled cells were identified as fibroblasts based on their spindle shape and fascicular concentric arrangement in tight perifollicular distribution. Although most of the LPP specimens (n = 35; 87.5%) also revealed cytoplasmic IL-17 expression in the lichenoid inflammatory infiltrate, the results were not statistically significant ( P = 0.1351). Conclusion: Our immunohistochemistry results show that blocking the IL-17 inflammatory pathway may interfere with the progression of the perifollicular fibrosis and inflammation in LPP.